Perlakuan Pupuk Organik dan Pupuk KP Terhadap Pertumbuhan, Hasil dan Kualitas Buah Stroberi Pada Tanah Gambut - Nurul Hidayati (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2019)
Strawberry (Fragaria sp) a part of Rosaceae family is fruit that have high economic value, and is very popular in Indonesia. Peat soils in Palangka Raya which have relatively acidic soil and high air temperatures are not agro-climately for strawberry plants. The use of Landrace strawberry varieties, organic and inorganic fertilizers are expected to produce quality strawberry production. The objectives of this study were (1) to find out the growth, yield, and level of sweetness of strawberries, (2) to get the right dose of organic fertilizer and KP fertilizer for strawberry cultivation, (3) to find out the sweetness level of lowland strawberries compared to the results of plateau (Java). This research was carried out in polybags located on Jl. Manjuhan Palangka Raya Central Kalimantan for 5 (five) months. This study was prepared using Factorial Randomized Completely Block Design (RCBD), consisting of two factors. The first factor was the use of doses of chicken manure (A) consisting of 3 levels namely: 20 tons / ha (A1), 40 tons / ha (A2), 60 tons / ha (A3), meanwhile the second were giving KP (M) inorganic fertilizers, consisting from 3 levels of concentration namely: 4 grams / liter (M1), 5 grams / liter (M2) and 6 grams / liter (M3). All of the treatments were replicated 3 times thus getting 27 unit of treatments. The results of this study were (1) The interaction of treatment of organic fertilizer with KP fertilizer had an effect on the variable number of leaves aged 28 HST, time of flower appearance, strawberry sweetness level, (2) The best treatment combination yields the sweetness of strawberries at 60 kg/ha and KP fertilizer at doses of 6 gr/l, and (3) Comparison of the quality of strawberry production from Palangkaraya with Java strawberries is still low in size, fruit diameter, but the sweetness of 0.13 brix times than strawberries from Java.